Effect of Field Experiences through Reflective Thinking on Self Esteem among Nursing Students - Kaiwikaikosol, Aryuporn (NU Journal of Nursing and Health Sciences, 2021)
This quasi-experimental research with two groups pretest-posttest design aimed to determine the effect of field experiences through reflective thinking on self-esteem of nursing students. Samples included 32 students of the 3rd year nursing students. Samples were purposively selected based on the inclusion criteria. They were randomly assigned into experimental group and control group, 16 subjects in each group. The experimental received reflective thinking technique as enhancing self-esteem. The control group received regular technique activity. Data were collected by using Rubin' s self-esteem scale. Its reliability was 0.88. Data were analyzed by using descriptive statistics and t-test. Results revealed that 1) After the intervention completed, self-esteem mean scores of students in the experimental group were non statistically significanthigher than those before intervention 2) Self-esteem mean scores of students in the experimental group were significantly higher than those in the control group (p < .05.) Therefore, field experiences through reflective thinking should be applied in other subjects in order to improve higher self-esteem of nursing studentscontinuously. This will enhance problem solving skills for their life problems and health care service problems effectively.